2010
DOI: 10.4113/jom.2010.1137
|View full text |Cite
|
Sign up to set email alerts
|

Geo-environmental cartography of the Marine Protected Area “Isola di Bergeggi” (Liguria, NW Mediterranean Sea)

Abstract: Marine Protected Areas (MPAs) are considered one of the main tools for conservation, valorisation and management of coastal marine environments, and are defined by Italian Law (derived from European directives) as territories with "physical, geological, geomorphological and biological features having relevant naturalistic and environmental value". While the bionomic mapping of MPAs has received large attention by researchers, MPA geological or geomorphological cartographies have been seldom realized. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The scientific knowledge (SCI) is heightened by the amount of scientific papers regarding geomorphological and bio-ecological features of the area, where early geomorphological studies date back to 1883 (Bianchi et al 1988;Carobene et al 2004;Forti 1992;Issel 1883;Morri et al 1994;Parravicini et al 2006Parravicini et al , 2008Parravicini et al , 2009Rovere et al 2007Rovere et al , 2008Rovere et al , 2009Rovere et al , 2010a. The aesthetic value (AEST) is slightly higher in the sites displaying deep plunging cliffs or rocky outcrops (North Bergeggi and South Bergeggi).…”
Section: Bergeggi Areamentioning
confidence: 96%
See 1 more Smart Citation
“…The scientific knowledge (SCI) is heightened by the amount of scientific papers regarding geomorphological and bio-ecological features of the area, where early geomorphological studies date back to 1883 (Bianchi et al 1988;Carobene et al 2004;Forti 1992;Issel 1883;Morri et al 1994;Parravicini et al 2006Parravicini et al , 2008Parravicini et al , 2009Rovere et al 2007Rovere et al , 2008Rovere et al , 2009Rovere et al , 2010a. The aesthetic value (AEST) is slightly higher in the sites displaying deep plunging cliffs or rocky outcrops (North Bergeggi and South Bergeggi).…”
Section: Bergeggi Areamentioning
confidence: 96%
“…In this field, getting inspiration from a methodological approach developed in France in the framework of the Habitat Directive (Bardat et al 1997), the Regional Activity Centre for Specially Protected Areas RAC SPA (UNEP) obtained evaluation indexes for 148 assemblage units (biocenoses, associations or facies) which correspond to the main marine habitats of the Mediterranean Sea (Bellan-Santini et al 2002;Relini 2000;UNEP MAP 1998). The combination of these criteria led to the realization, in the last decade, of marine territorial cartographies of Mediterranean protected areas (Rovere et al 2010a). Bianchi (2007), following the conceptual schemes proposed by Bianchi and Zurlini (1984), defined marine natural emergencies as species, habitats or landforms of conservation interest, achieving the result of a territorial cartography displaying three kinds of naturalistic emergencies: biological (species), ecological (habitats), and geomorphological (landforms).…”
Section: Introductionmentioning
confidence: 99%
“…Underwater SCUBA transects were carried out down to − 20 m to identify the occurrence of submerged sea-level markers following the methodologies proposed by Collina-Girard (2002) and Rovere et al (2011a). Depth was measured using a 3 m metal bar (in shallow water) and averaging 2 accurate electronic depth gauges with a final precision of 0.5 m (at depths ≥ −3 m, Rovere et al, 2010). Readings were noted using a PVC slate.…”
Section: Sea Level Markersmentioning
confidence: 99%
“…Cartography not only represents the spatial location of marine habitats and geomorphic features (Miccadei, Orru, Piacentini, Mascioli, & Puliga, 2012;Rovere et al, 2010;Sardá, Rossi, Martí, & Gili, 2012), but also allows, through the use of geographic information systems (GIS), the modeling of different management scenarios (Fraschetti et al, 2005;Montefalcone et al, 2013;Parravicini et al, 2012;Vassallo, Paoli, Rovere, & Montefalcone, 2013). Mapping of terrestrial information is largely reported in the literature (Finn, 2011;López-García & Guzmán, 2010;Rose & Smith, 2008;Sahlin & Glasser, 2008), and takes advantage of numerous survey techniques such as satellite imagery, aerial photos, LIDAR or high-accuracy GPS (Bowles & Cowgill, 2012;Palamara, Dickson, & Kennedy, 2007;Storrar, Stokes, & Evans, 2013).…”
Section: Introductionmentioning
confidence: 99%